Programa educativo de relaciones interpersonales “JANA” y clima institucional de una I.E en Carmelo de Virú, 2018 - Arenas Benavides, Jackeline (2018)
The purpose of this research work was the purpose of educational education, interpersonal relations, writing, regular quality, improvement of the institutional climate and educational education. . This is the population of educational institutions in the rural area of Virú district province of Virú, La Libertad department. The Alternative Training Rural Center (CFRA) "El Carmelo" of the Viru district was chosen as a sample. It is a preexperimental design of a single group already formed, with the exam and the posttest, to test the hypothesis that the application of the program aims to improve the institutional climate in the educational institution of the study. The qualification of the institutional climate was based on the perception of the managerial staff and the teaching about said climate, through a survey using a questionnaire on the institutional climate adapted by the authors. Contrary to the hypothesis of the study using the Wilcoxon test for two samples related to α = 0.05, it is concluded that the educational program of interpersonal relationships is applied to the leaders and teachers of an educational education. Institutional climate in that educational institution, given that, the value - p = 0.002 obtained less than α = 0.05, draws up the null hypothesis put forward. Likewise, the results are shown as the educational program and interpersonal relationships are applied, the level of the institutional climate is improved in its considered dimensions: communication, motivation, trust and participation, taking into account that, before the implementation of the program of As a reference, the management and teaching staff predominantly qualified these dimensions, such as the low level and after the application of the aforementioned program, he qualified as high level.